Optimum algorithms of division two mutually unortogonal signals (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
«Base» algorithms are considered coherent, kvazikogerentnogo and un-coherent – autocorrelation division of useful digital signal and similar to him unortogonal hindrance which exceeds an useful signal on instantaneous power. Under un-coherent treatment of signals  is  understand  a  situation,  when  one  of  two  vzaemnozavazhayuchikh  signals demodulyuet'sya coherently (kvazikogerentno), and second – non-coherent (autocorrelation). Practical application of these algorithms allows to realize the repeated use of frequencies, busy at powerful radiations, – for example, on the second basis. Thus a basic user at some additionalss can even and not to notice the fact of the repeated use of frequencies.